Rhabillez-moi ! Stratégies sur mesure dans la réhabilitation de cinq immeubles de logements postmodernes parisiens - Julien Correia (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The book Paris Postmoderne, published in 2023, highlights the large number of Parisian buildings from the 1973-1993 period that are often visible but generally unknown. In proposing this inventory, Jean-Louis Violeau invites us to reflect on the future of this built heritage. Many of them are residential buildings that are currently undergoing a rehabilitation campaign, generally aimed at resolving thermal problems through systematic intervention on the building envelope.Improving comfort and usage by renovating common areas and wet rooms may also be included in the specifications. The issues raised by this type of program are manifold : they involve both theoretical and technical positioning regarding the design and materiality of facades. They also call into question the unilateral decision to intervene solely - but nonetheless imposingly - on the envelope, considering other components of the buildings (structure, housing composition, etc.), which are often absent from the programmatic question posed.The varied formal language and abundance of details that sometimes tend to over-complexify what are otherwise simple, ordinary buildings are now being challenged by the need to thermally insulate these buildings while guaranteeing their durability of use and character. This article offers a reflective analysis of the practice of the Parisian architectural firm Jean-Marin et asssocié.es, based on five case studies : the corner building at 31 rue des Malmaisons, 97-105 rue de la Jonquières, 11 rue Duris, Cour du Liégat and Hautes Formes. As projects are developed, the first stages of which date back to 2016, responses are adapted. It’s a matter of questioning the offices’s acculturation to postmodern architecture as much as the implicit emergence of a project methodology.